Engaging the public in science crowdfunding: Scientists calling to action through visual and verbal strategies - Vivas-Peraza, Ana Cristina (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Crowdfunding is a collaborative funding strategy increasingly used by scientists to finance their research projects. It involves raising small donations from the online public, which challenges scientists to create engaging crowdfunding proposals in digital platforms. These proposals become more persuasive with a short video promoting the project and arguing why it deserves funding. By adopting a multimodal approach, this paper explores the visual and verbal engagement strategies used in those videos, to observe how scientists exploit different semiotic resources to reach out to the public and call them to action.